What are the smallest moths (Lepidoptera) in the world? - Stonis, Jonas R.; Remeikis, Andrius; Diškus, Arūnas; Baryshnikova, Svetlana; Solis, M. Alma (Zootaxa, 2021)
The world’s smallest moths in Lepidoptera (Insecta) and the complexity in making such a determination are examined and discussed. The forewing length and wingspan of 650 species were measured and the same data were retrieved from published papers to determine which species and family have the smallest moths in the world. The minimal recorded forewing length was found to be around 1.2–1.3 mm and the wingspan around 2.6–2.8 mm in two families, the Gracillariidae and Nepticulidae. Among Lepidoptera, the following species have the smallest moths globally: the European Johanssoniella acetosae (Stainton), the Peruvian Simplimorpha kailai Stonis & Diškus, the Mexican Stigmella maya Remeikis & Stonis, the Mediterranean S. diniensis (Klimesh), the Mediterranean Parafomoria liguricella (Klimesh) (Nepticulidae), the South East Asian Porphyrosela alternata Kumata, and the Central African P. desmodivora De Prins (Gracillariidae). Additionally, in the Nepticulidae, we provide a measurement update for Stigmella maya Remeikis & Stonis, one of the tiniest species with a forewing length of 1.3 mm and wingspan of 2.8 mm, and describe a new species, Stigmella incaica Diškus & Stonis, sp. nov., with a forewing length of 1.75 to 1.95 mm and a wingspan of 3.8 to 4.3 mm.